Objective Assessment of Sleep Disorders in Patients with Lumbar Spinal Stenosis Using Wearable Trackers - Masahiro Inoue; Sumihisa Orita; Kazuhide Inage; Miyako Suzuki-Narita; Yasuhiro Shiga; Hideyuki Kinoshita; Masaki Norimoto; Tomotaka Umimura; Yawara Eguchi; Tsutomu Akazawa; Yasuchika Aoki; Yuki Shiko; et al. (Spine Surgery and Related Research, 2023)
Introduction: Low-back pain causes sleep disorders, which impairs the quality of life (QOL) of patients. Sleep disorders are associated with lumbar spinal stenosis (LSS); however, the postoperative effects of LSS surgery on sleep disorders are unknown. This study aimed to assess sleep disorders in patients with LSS using wearable activity trackers and determine whether surgery improves sleep quality. Methods: A total of 39 patients scheduled for LSS surgery (mean age 71.1±8.7 years; 22 men and 17 women) were studied. Sleep disorders in the participants were objectively evaluated using a wearable Motionlogger Micro system. Sleep efficiency (SEf), mean active count (MAC), and wake after sleep onset (WASO) were measured before and 6 months following surgery. Furthermore, the patient-based outcomes of pain and QOL-related scores were measured and compared with those of healthy participants. The group with improved SEf following surgery was designated as “nonpoor sleepers,” whereas the group that did not exhibit improvements was designated as “poor sleepers.” The two groups were compared based on patient factors, patient-based questionnaires, and sleep disorder measurements. Results: The SEf and WASO were significantly worse in patients with LSS compared with healthy participants (P<0.05). Furthermore, the SEf in patients with LSS was associated with the Oswestry Disability Index scores. No improvement was observed in the SEf, MAC, and WASO before and after surgery. Evaluation of each case revealed 21 and 12 cases of nonpoor and poor sleepers, respectively. Preoperative low-back pain was significantly associated with improvement in postoperative sleep quality. Conclusions: Sleep disorders in patients with LSS were evaluated, and improvement in sleep disorders following surgery was associated with the intensity of preoperative low-back pain. Sleep disorders are associated with QOL disorders, suggesting that focusing on the treatment of sleep disorders is important in the management of patients with LSS.